Development of an Instrument for Assessing Risk of Bias of Randomized Trials in Systematic Reviews - Wang, Ying (My University, 2024)
Assessment of risk of bias in the included randomized controlled trials (RCTs) has become an essential step in systematic reviews, which informs the decision of whether to rate down certainty of evidence due to risk of bias applying the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Many instruments exist for rating risk of bias in RCTs; however, even those most commonly used that developed by the Cochrane group, suffer from limitations. In particular, the revised Cochrane instrument, while reflecting methodological advances, sacrificed simplicity and practicability. The objective of this thesis is to use rigorous methodology to develop a simple-structured RCT risk of bias instrument that is easy for systematic review authors to use. The thesis begins with a chapter introducing the background and the structure of the thesis. The thesis subsequently describes a systematic survey of existing RCT risk of bias instruments for their included items, through which we collected potential candidate items for the new instrument. We then present a summary of empirical evidence investigating how the possible risk of bias issues influence the estimates of intervention effects in RCTs, which assisted with the item selection for the new instrument. Then, this thesis describes the detailed process for instrument development and providing the new instrument. This thesis ends with a chapter summarizing key findings, discussing strengths and limitations, and exploring directions for future research.
Keywords: Risk of Bias Assessment; Risk of Bias Instrument; Randomized Trials; Systematic Review